Menelusuri Jejak Bibliometrik Digital Entrepreneurial Intention: Peta Tematik dan Distribusi Global 2011–2025 - Febrianti, Dika Melia; Martono, Trisno (Universitas Hamzanwadi, 2025)
Research on digital entrepreneurial intention (DEI) has grown significantly over the past decade; however, systematic mapping of its trends, scholarly collaborations, and thematic structures remains limited. This study aims to map the development of scientific publications, thematic distribution, and influential contributors in DEI research using a bibliometric approach. A total of 236 articles from the Scopus database covering the years 2011–2025 were analyzed using the PRISMA method, supported by Microsoft Excel, Publish or Perish, and VOSviewer for data visualization. The results indicate a sharp increase in DEI-related publications since 2021, with key themes including digital literacy, self-efficacy, entrepreneurship education, and the Theory of Planned Behavior. Students emerged as the most frequently studied population within this field. Furthermore, the study identifies the most productive countries, authors, and journals contributing to DEI research. These findings provide a comprehensive overview of the intellectual landscape of digital entrepreneurship and offer a foundation for developing policy and educational strategies in digital entrepreneurship.